Application of neurotoxin- and pesticide-induced animal models of Parkinson’s disease in the evaluation of new drug delivery systems - Casanova Yaquelyn; Negro Sofia; Barcia Emilia (Acta Pharmaceutica)
Parkinson’s disease (PD) is the second most prevalent neuro-degenerative disease after Alzheimer´s disease. It is characterized by motor symptoms such as akinesia, bradykinesia, tremor, rigidity, and postural abnormalities, due to the loss of nigral dopaminergic neurons and a decrease in the dopa-mine contents of the caudate-putamen structures. To this date, there is no cure for the disease and available treatments are aimed at controlling the symptoms. Therefore, there is an unmet need for new treatments for PD. In the past decades, animal models of PD have been proven to be valuable tools in elucidating the nature of the pathogenic processes involved in the disease, and in designing new pharmacological approaches. Here, we review the use of neurotoxin-induced and pesticide-induced animal models of PD, specifically those induced by rotenone, paraquat, maneb, MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) and 6-OHDA (6-hydroxydopamine), and their application in the development of new drug delivery systems for PD.